2014
DOI: 10.1111/bor.12085
|View full text |Cite
|
Sign up to set email alerts
|

Holocene environmental change in theSkallingen area, easternNorthGreenland, based on a lacustrine record

Abstract: A lacustrine record from a small lake, Lille Sneha Sø, in the Skallingen area indicates that the region was deglaciated in the early Holocene, prior to 8000 cal. a BP. Deglaciation was probably triggered by high temperatures, but it took more than 1000 years for the lake and the catchment to stabilize. Chironomids were amongst the first invertebrates to colonize the lake. The fossil chironomid assemblage is fairly rich and comparable to other records from further south in Greenland. The pioneer vegetation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Studies of chironomid assemblages in surface sediments along spatial and climatic transects have repeatedly demonstrated that temperature is a dominant predictor of chironomid species distributions (e.g. Pioneering qualitative palaeoclimate interpretations from chironomid assemblages have been published for several sites in eastern and northeastern Greenland (Wagner et al 2005;Schmidt et al 2011;Wagner & Bennike 2015). Pioneering qualitative palaeoclimate interpretations from chironomid assemblages have been published for several sites in eastern and northeastern Greenland (Wagner et al 2005;Schmidt et al 2011;Wagner & Bennike 2015).…”
mentioning
confidence: 99%
“…Studies of chironomid assemblages in surface sediments along spatial and climatic transects have repeatedly demonstrated that temperature is a dominant predictor of chironomid species distributions (e.g. Pioneering qualitative palaeoclimate interpretations from chironomid assemblages have been published for several sites in eastern and northeastern Greenland (Wagner et al 2005;Schmidt et al 2011;Wagner & Bennike 2015). Pioneering qualitative palaeoclimate interpretations from chironomid assemblages have been published for several sites in eastern and northeastern Greenland (Wagner et al 2005;Schmidt et al 2011;Wagner & Bennike 2015).…”
mentioning
confidence: 99%
“…A third overlapping sediment core below 105 cm composite depth (obtained using the Russian corer) revealed silty and sandy sediments, which according to the results from studies of nearby Lille Sneha Sø (Figs 1, 2) most likely represent the deglaciation of the area (Wagner & Bennike 2015). However, radiographic scanning with an ITRAX core scanner (Cox Co., Sweden) allowed optical correlation of the sediment cores.…”
Section: Methodsmentioning
confidence: 82%
“…The most common are worn stem fragments of the bryophyte Scorpidium scorpioides. As mentioned by Wagner & Bennike (2015), L. arcticus is fairly widespread in Greenland, but it has not been found in the northernmost parts, including the Trifna Sø area. Scorpidium scorpioides may be characterized as fairly warmthdemanding because it is very rare in North Greenland (Holmen 1960).…”
Section: Stratigraphymentioning
confidence: 94%
See 2 more Smart Citations